Investigations on the structural and optoelectronic characteristics of cadmium-substituted zinc selenide semiconductors - Iqbal, Muhammad Aamir; Bakhsh, Sunila; Ikram, Mujtaba; Sohail, Muhammad; Islam, Md. Rasidul; Manoharadas, Salim; Choi, Jeong Ryeol (Frontiers in Chemistry, 2023)
The change in composition and dopant content of selective atoms in a material leads to their new desired properties by altering the structure, which can significantly improve the performance of relevant devices. By acknowledging this, we focused on characterizing the optoelectronic and structural properties of cadmium-substituted zinc selenide (Zn1-xCdxSe; 0 ≤ x ≤ 1) semiconductors by employing density functional theory (DFT) within the GGA, EV-GGA, and mBJ approximations. The results proved the cubic symmetry of the investigated materials at all the concentrations of Cd (0, 0.25, 0.50, 0.75, and 1). Although a linear surge in the lattice constant has been observed with the change in the Cd content, the bulk modulus exhibits a reverse trend. These materials are noticed to remain direct bandgap semiconductors at all Cd concentrations with a decrease in electronic bandgap from 2.76 eV to 1.87 eV and have isotropic optical properties, showing their potential applicability as a blue-to-red display. The fundamental optical properties of the materials, such as optical conductivity, reflectance, refractive index, absorption, and extinction coefficient, are also discussed. These outcomes provide a computational understanding of the diverse applications of Zn1-xCdxSe semiconductors in optoelectronic, photonic, and photovoltaic devices, especially for a visible-range display.